2003
DOI: 10.1021/ma025879c
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Templating of Islands and Holes in Highly Asymmetric Block Copolymer Films

Abstract: Asymmetric diblock copolymers with a spherical domain structure form islands or holes on the free surface of a thin film when the initial spun-cast film thickness does not match that of an integral number of layers of spheres plus a brush. When this film is cast on a substrate topologically patterned with rectangular, flat bottomed wells as deep as a layer of spheres, the edges of these wells act as sinks for excess material. As a result, we observe the movement of material away from the raised areas (mesas) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 51 publications
1
63
0
Order By: Relevance
“…Heier et al have succeeded in templating surface domain structures on smooth substrates that were chemically patterned by microcontact printing on a scale of 1-16 mm [141]. Similar patterning of island and holes has been shown for sphere-forming [142] and lamellar [143] block copolymers on a topographically patterned substrates. Several more studies have investigated the effect of surface patterning on block copolymer orientation and order and these will be discussed later in this review.…”
Section: Film Thicknessmentioning
confidence: 79%
See 2 more Smart Citations
“…Heier et al have succeeded in templating surface domain structures on smooth substrates that were chemically patterned by microcontact printing on a scale of 1-16 mm [141]. Similar patterning of island and holes has been shown for sphere-forming [142] and lamellar [143] block copolymers on a topographically patterned substrates. Several more studies have investigated the effect of surface patterning on block copolymer orientation and order and these will be discussed later in this review.…”
Section: Film Thicknessmentioning
confidence: 79%
“…Initially, islands and holes form on top of the topographically patterned substrate. In a manner similar to that described earlier in this review for sphere-forming block copolymers [142], material flows from the tops of the mesas to fill the channels. In this case, however, transport may take place via a mass flow along the cylinder axis.…”
Section: Epitaxymentioning
confidence: 86%
See 1 more Smart Citation
“…30,31,[43][44][45][46][47][48][49] However, for the much faster process of solvent annealing and evaporation under controlled humidity, chains must diffuse and reorganize within a time several orders of magnitude shorter than those used for thermal processing. Under such conditions, the surface and interior reconstruction is unlikely to result in an equilibrium structure.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,[23][24][25][26] Several studies have examined the structure and dynamics of defects of BCP thin films on homogeneous surfaces. [27][28][29][30][31][32][33] Structural evolution on chemically patterned surfaces, however, is significantly different from that observed on homogeneous substrates. 26 Welander et al, for example, have shown that annealing at elevated temperatures leads to formation of defect-free structures in a matter of minutes.…”
Section: Modeling and Simulationmentioning
confidence: 84%